2016
DOI: 10.1038/srep33350
|View full text |Cite
|
Sign up to set email alerts
|

Effects of captivity and artificial breeding on microbiota in feces of the red-crowned crane (Grus japonensis)

Abstract: Reintroduction of the threatened red-crowned crane has been unsuccessful. Although gut microbiota correlates with host health, there is little information on gut microbiota of cranes under different conservation strategies. The study examined effects of captivity, artificial breeding and life stage on gut microbiota of red-crown cranes. The gut microbiotas of wild, captive adolescent, captive adult, artificially bred adolescent and artificially bred adult cranes were characterized by next-generation sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 55 publications
10
33
0
Order By: Relevance
“…In terms of similarities, we found that the crane gut microbiota, regardless of host species, was primarily composed of taxa in the phylum Firmicutes (76%). The dominance of Firmicutes is consistent with previous descriptions of crane gut microbiota [46,47] and the avian gut microbiome in general [11]. However, cranes in our study harboured a higher relative abundance of Firmicutes compared with the previous studies of crane gut microbiota [46,47] and was similar to that reported in mammals [48,49].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In terms of similarities, we found that the crane gut microbiota, regardless of host species, was primarily composed of taxa in the phylum Firmicutes (76%). The dominance of Firmicutes is consistent with previous descriptions of crane gut microbiota [46,47] and the avian gut microbiome in general [11]. However, cranes in our study harboured a higher relative abundance of Firmicutes compared with the previous studies of crane gut microbiota [46,47] and was similar to that reported in mammals [48,49].…”
Section: Discussionsupporting
confidence: 92%
“…The dominance of Firmicutes is consistent with previous descriptions of crane gut microbiota [46,47] and the avian gut microbiome in general [11]. However, cranes in our study harboured a higher relative abundance of Firmicutes compared with the previous studies of crane gut microbiota [46,47] and was similar to that reported in mammals [48,49]. While the potential effects of Firmicutes on crane physiology are currently unknown, studies in mammals [50] and chickens [51] have demonstrated that Firmicutes are important to host metabolism and digestive health, most likely through their ability to produce short-chain fatty acids through the breakdown of dietary carbohydrates and polysaccharides [52].…”
Section: Discussionsupporting
confidence: 90%
“…At the phylum level, Proteobacteria was the predominant phylum in all GIT segments. Proteobacteria are facultative anaerobes and have been found to be the dominant phylum in the gastrointestinal tract of some fish (Givens, Ransom, Bano, & Hollibaugh, ), snakes (Colston et al, ), and birds (Xie et al, ). These bacteria typically breakdown and ferment complex sugars, and Escherichia may be important in the production of vitamins for the host (Colston & Jackson, ).…”
Section: Discussionmentioning
confidence: 99%
“…The roles of environmental exposure and diet in shaping the host microbiome may cause the gut microbiome to act as an important mediator for how urban environments or changing diets may affect host health. The shifts in diet and habitat exhibited by wildlife in urban environments likely influence their gut microbial communities as they do for animals in captivity [15][16][17][18] and humans in urban vs. rural communities [19]. While a rapidly growing body of literature has characterized the avian microbiome for many species [20], little is known about how the novel foods and habitat types available to urban birds may shape microbiome diversity and composition.…”
Section: Introductionmentioning
confidence: 99%